Korelasi antara motivasi belajar dengan kemampuan pemecahan masalah matematik peserta didik menggunakan model problem based learning (PBL) - Yeni Heryani; Subaru Utama Olpado (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2017)
This study aims to determine the learning motivation of learners using Problem Based Learning (PBL) model, the ability to solve mathematical problems of learners using the Problem Based Learning (PBL) model, and the correlation between learning motivation and mathematical problem-solving skills of students using Model of Problem Based Learning (PBL). The method used is correlation method and descriptive method. The population in the study were all students of class VIII SMP Negeri 9 Tasikmalaya, academic year 2015/2016. The sample in this study selected one class at random from all members of the population. The selected sample is class VIII B. The instrument used in the research is a matter of mathematical problem-solving abilities on the material of flat side room consisting of 4 items, and a set of the statement of motivation questionnaire as many as 18 items statement. The problem-solving and questionnaires test of learning motivation is carried out at the end of the lesson after all the materials are delivered. To analyse the results of research using statistical tests of regression and correlation between variables. Based on the results of research, processing, data analysis, and hypothesis testing it can be concluded that the ability of problem-solving mathematics learners using learning model of Problem Based Learning (PBL) included in good category, learning motivation of learners using Problem Based Learning model (PBL ) Included in medium motivation category, and there is correlation between learning motivation with problem-solving ability of mathematic learners using Problem Based Learning (PBL) model.